1994
DOI: 10.1161/01.cir.90.5.2199
|View full text |Cite
|
Sign up to set email alerts
|

Deletion polymorphism of the angiotensin I-converting enzyme gene is associated with serum ACE concentration and increased risk for CAD in the Japanese.

Abstract: A deletion polymorphism of the ACE gene is associated with serum ACE activity and increased risk for CAD in the Japanese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
96
1
7

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(122 citation statements)
references
References 21 publications
18
96
1
7
Order By: Relevance
“…12 Since that time a lot of studies were performed in which ACE genotype was used as a tool, through association studies, to investigate the role of tissue ACE in human disease pathogenesis. [13][14][15][16][17] Taken together, the available evidence supports the notion that the DD ACE genotype adversely influences specific cardiovascular diseases but appears to do so in specific geographical areas and in particular patient subgroups. 18 This can be a possible explanation of the inconsistency of association between ACE genotype and ED.…”
Section: Introductionsupporting
confidence: 62%
“…12 Since that time a lot of studies were performed in which ACE genotype was used as a tool, through association studies, to investigate the role of tissue ACE in human disease pathogenesis. [13][14][15][16][17] Taken together, the available evidence supports the notion that the DD ACE genotype adversely influences specific cardiovascular diseases but appears to do so in specific geographical areas and in particular patient subgroups. 18 This can be a possible explanation of the inconsistency of association between ACE genotype and ED.…”
Section: Introductionsupporting
confidence: 62%
“…Therefore, control genotyping assays are mandatory in presumed DD carriers (Lin et al 2001). Mechanistically, the D allele is associated with increased levels (approximately twofold in homozygous carriers) of ACE in Caucasian and Asian but not in African populations (Rigat et al 1990;Nakai et al 1994;Bloem et al 1996). Other groups have confirmed that this polymorphism accounts for half of the observed variance in ACE plasma levels.…”
Section: Polymorphisms In the Angiotensin Converting Enzymementioning
confidence: 99%
“…These findings have also been shown in other populations, even in prospective studies. 10,11 However, not all studies have demonstrated this association. 12,13 There are few studies that have investigated the association between BMI, ACE gene I/D polymorphism and CHD.…”
Section: Introductionmentioning
confidence: 99%